The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.2147/cmar.s300574
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Fibrinogen–Albumin Ratio, Potential Prognostic Factors for Bladder Cancer Patients Undergoing Radical Cystectomy: A Two-Center Study

Abstract: Background:We conducted a two-center study to investigate the prognostic value of preoperative fibrinogen-albumin ratio (FAR) in patients undergoing radical cystectomy (RC). Methods: The clinical and survival data of 267 patients with bladder cancer (BCa) treated with RC were collected, of which 140 patients from Xuzhou Central Hospital were divided into training set and 127 patients from The Second Affiliated Hospital of Nantong University were divided into validation set. X-tile software was used to obtain t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…As usually, low level of albumin commonly indicated malnutrition and cachexia in malignant tumor patients, which are closely correlated with worse prognosis. 30 Similar to our results, the FAR, as a new biomarker combining with blood nutritional status and blood coagulation function, has already been proven as a valuable prognostic factor in the prediction of prognosis of various malignancies, such as HCC, ICC, pancreatic cancer, etc. 21 , 22 , 31 …”
Section: Discussionsupporting
confidence: 88%
“…As usually, low level of albumin commonly indicated malnutrition and cachexia in malignant tumor patients, which are closely correlated with worse prognosis. 30 Similar to our results, the FAR, as a new biomarker combining with blood nutritional status and blood coagulation function, has already been proven as a valuable prognostic factor in the prediction of prognosis of various malignancies, such as HCC, ICC, pancreatic cancer, etc. 21 , 22 , 31 …”
Section: Discussionsupporting
confidence: 88%
“…Hwang et al evaluated the prognostic influence of preoperative FAR in breast cancer, reporting a worse prognosis for patients with a higher FAR (>7.1) [ 21 ]. Analogously, a study by Xu et al reported unfavorable overall survival in gall bladder cancer patients with FAR > 0.08 compared to patients with lower values [ 33 ]. Finally, An et al reported high FAR (>7.75) as a worse prognostic factor in cervical cancer [ 20 ].…”
Section: Discussionmentioning
confidence: 79%
“…In recent years, there have been continuous studies to explore the relationship between FAR and the clinical outcome of human solid tumors ( 29 , 35 , 36 , 39 ). FAR is expected to be a simple, inexpensive, and readily available biomarker for predicting clinical prognosis in patients with solid tumors.…”
Section: Discussionmentioning
confidence: 99%